Constituição, formulação e circulação do discurso jurídico: a designação dano moral produzindo efeitos de sentido - Silva, Marcelo da (2006)
The main objective in this work is to understand how the juridical practice, through the discursive relations established in a specific lawsuit, produces sense effects, and how the same and the different relate to each other in the juridical discursivity. In order to do this, we have analyzed the processual rite of an indemnity ordinary action for losses and damages and moral damage, filed in the third civil jurisdiction of the judicial district of Santa Maria-RS, from the theoretical principles of French Discourse Analysis or according to a materialistic point of view. The analysis has as a starting point the designation moral damage and the corpus comprises the following lawsuit elements: initial petition, contestation, replication and sentence. From the necessary theoretical mobilization for the reflection and by means of analysis of the discursive corpus we can understand that this discursivity is organized in a way to try to regulate the meanings of moral damage. This happens from a particularization and generalization process which mediates the organization of the documents and intends to regulate the senses, creating an illusion of applicability of the rules of law to the conducts presented in the documents. However, this language functioning is not free of imperfections, since ruptures and displacements happen in this attempt of regulation. This happens through the established game between two distinct forms of subject s individuation, called religious subject and subject-of-right (HAROCHE, 1992). On one side, we have the interchangeability, which aims at to support the regulation of the senses and the applicability of the law. On the other side, we have the expression of the subjectivity, which makes possible that the conducts presented in the documents be brought for discussion (making possible the discussion of exterior questions related to the legal system). We understand that even though the juridical discourse opens space for the movement of the senses, this is constituted in a way to regulate itself. The juridical discourse is formulated and it circulates, respecting a series of rules that delimit what can and must be said, then supporting and legitimizing this discursivity.